La facultad de los jueces al ordenar pruebas de oficio en materia civil, y su contradiccion con el derecho constitucional del debido proceso - Toalumbo Valiente, Jorge Alberto (2014)
This legal research is about the ability of judges to order tests motion at any stage of the judicial process in the first chapter there is information about the administration of justice in our country, and its supreme end achieve good common, the same as fully identifies with other rights, such as justice, freedom, peace, order and security, that society trusts the institutions responsible for the administration of justice. The second chapter begins with the background research, ie with constitution, principles, materials, consulting, steps and measures, among others trying to secure the right to due process. In the third chapter, begins with the methods used in the research, in this chapter the analysis, interpretation and the results of the survey, interview and representative graphics set. In the fourth chapter, the findings and results with judges to order tests for office, as required by Section 118 of the Code of Civil Procedure, which is essential to the administration of justice that there is policy incoherence among listed the Constitution and the Code of Civil Procedure rule since the burden of proof is on the litigants. The proposed reform of Article 118 of the Code of Civil Procedure Ecuador, the synthesis of business, objectives, and description of the proposal, beneficiaries and the social impact of this reform is demonstrated in the fifth chapter.